Differences by gender and school of origin on interpersonal communication - Arenas Iparraguirre, Carlos (2012)
This study had the objective to identify the differences by gender and kind of school in interpersonal communication, the sample comprised of 181 university students, the study design was descriptive and comparative, the questionnaire was used interpersonal communication of Reyes (1996), extracted the validity and reliability for the study, the results show no statistically significant differences by gender and type of school in interpersonal communication, it highlights the need for studies on interpersonal communication in Latin America related to social and technological.